2009
DOI: 10.3168/jds.2008-1299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rumen-protected choline and dry propylene glycol on feed intake and blood parameters for Holstein dairy cows in early lactation

Abstract: A 6 x 6 Latin square design was used to test 3 sets of comparisons simultaneously to study response in dry matter intake, milk yield, and blood parameters to propylene glycol (PG) supplementation delivered by 2 methods [incorporating PG into the total mixed ration (TMR) vs. top dressing; comparison I]; individual or combined dietary choline and PG supplementation as a 2 x 2 factorial (comparison II); or increasing amounts of dietary choline (comparison III). Six multiparous (lactation number = 1.5 +/- 0.8 SD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 29 publications
5
37
2
Order By: Relevance
“…In dairy cattle, Pinotti et al (2004) observed a significant increase of plasma cholesterol and a NEFA decrease with a tendency for increased glucose with an estimated effective duodenal dose of 75 mg/kg BW 0.75 . In contrast, Chung et al (2009) did not find an effect on plasma NEFA and glucose in dairy cows dosed with an estimated effective 73 or 147 mg/kg BW 0.75 . Nor did Zhou et al (2016), who observed changes in glucose or fatty acids with estimated flows from 72 or 80 mg/kg BW 0.75 .…”
Section: Fermentation Gas Parametersmentioning
confidence: 64%
“…In dairy cattle, Pinotti et al (2004) observed a significant increase of plasma cholesterol and a NEFA decrease with a tendency for increased glucose with an estimated effective duodenal dose of 75 mg/kg BW 0.75 . In contrast, Chung et al (2009) did not find an effect on plasma NEFA and glucose in dairy cows dosed with an estimated effective 73 or 147 mg/kg BW 0.75 . Nor did Zhou et al (2016), who observed changes in glucose or fatty acids with estimated flows from 72 or 80 mg/kg BW 0.75 .…”
Section: Fermentation Gas Parametersmentioning
confidence: 64%
“…Absence of a plasma constituent response to choline supplementation has also been reported in transition dairy cows (Piepenbrink and Overton, 2003;Janovick Guretzky et al, 2006). Other studies however have reported lower plasma NEFA in choline-supplemented animals around parturition (Pinotti et al, 2003;Chung et al, 2005) or during the dry period (Grummer, 2006); Zahra et al (2006) found lowered serum cholesterol. Thus further studies are needed to clarify the mechanism of action of choline on plasma metabolites in periparturient dairy ruminants.…”
Section: Resultsmentioning
confidence: 86%
“…Several strategies have been attempted to reduce the effects of NEB, including supplementation with glycerol (DeFrain et al, 2004), nicotinic acid (Pires et al, 2007), cis-linoleic acid (Mosley et al, 2007), fat (Moallem et al, 2007), methionine (Preynat et al, 2009), choline (Chung et al, 2009), carnitine (Carlson et al, 2007) and monensin (Duffield et al, 2008). Overall, current treatments had limited success, and more research is needed.…”
Section: Introductionmentioning
confidence: 99%